Preservation of Library Materials: Problems and Perspective - Sunil, Adupa; Praveen Kumar, K. (DESIDOC Journal of Library & Information Technology, 2010)
In any civilised society library has a significant place for study, research, reference, and recreation. It is a product of cultural maturation and storehouse of knowledge. Libraries extend horizons of knowledge. The large-scale explosion of information has necessitated libraries to not only be well-stocked and wellorganised, but also to collect non-book materials such as motion picture, slides, magnetic tapes, CDs, DVDs, etc. The preservation of these multifarious materials has necessitated changes in the form of preservation efforts. This paper gives an overview of how to conserve library material. http://dx.doi.org/10.14429/djlit.29.260